“I am not that sick”The use of Assistive Mobility Technologies among theElderly - Rehema Bavuma Namaganda; Kyaddondo David; Kiwuwa Steven; Kajja Isaac (Journal of Aging Research And Healthcare, 2017)
The use of mobility assistive technologies in different contexts seem to give a great promise to potentially improve mobility, functionality, social interaction as well as performance of daily activities for the elderly. Unused wheelchairs and abandoned crutches however were a common scene in the homes of the elderly people during this study. This paper presents stories of three elderly people from a bigger study on aging and the use of assistive technologies, drawing attention to the need for proper understanding and appreciation of the context before assistive technologies are assigned especially in old age.
Keywords: Aging